Analisis Produktivitas dan Income Over Feed Chick Cost (IOFCC) Ayam Ras Pedaging yang Dipelihara dalam Kondisi Heat Stress Menggunakan Kunyit (Curcuma domestica) pada Air Minum - Candra, A A; Putri, D D; Oktyana, S N (PETERPAN (Jurnal Peternakan Terapan), 2024)
This study aims to analyze the productivity of broilers kept in heat stress conditions by giving drinking water mixed with turmeric (Curcuma domestica). This research was conducted in the Lampung State Polytechnic cage and carried out in February 2024. In this study using the experimental method by comparing the turmeric treatment group as much as 500 mg / kg of chicken body weight which will be compared with the group without treatment (control). The results of the research on the provision of drinking water given turmeric (Curcuma domestica) to broilers kept in heat stress conditions have not been able to optimize the effectiveness of broiler productivity and have not been able to increase the effectiveness of Income Over Feed Chick Cost (IOFCC) with the results of the heat stress index declared dangerous.